Will TARGET2-Balances be Reduced again after an End of the Crisis? - Christian Fahrholz; Andreas Freytag (Graduiertenkolleg 'Konstitutionelle Grundlagen globalisierter Finanzmärkte - Stabilität und Wandel', 2012)
This article deals with the macro-economics of the Trans-European Automated Re- al-time Gross Settlement Express Transfer System (TARGET2). Originally, the TARGET2 was in-tended to solely function as a monetary arrangement for liquidity issues. It is shown that the TARGET2 contributes to a substantial misallocation of real resources within the Eurozone (EZ). The discussion highlights that there are no tendencies for rebalancing TARGET2-claims and liabilities, but rather a dynamic towards infinite and prolonged TARGET2-imbalances in the form of hysteresis.
urn:nbn:de:gbv:27-20131126-140009-8
Keywords: E02; E42; E44; E63; H63; 330; TARGET2; Eurosystem; ESCB; balance-of-payments; Internationaler Zahlungsverkehr; Clearing; Hysteresis; Eurozone; Eurozone